EXPLORING DIGITAL WAQF IN INDONESIA: STRATEGY FOR OPTIMIZING ACCOUNTABILITY AND TRANSPARENCY - Latiefa Salsabila, Fauziyah; Rini; Soelistiyono, Anitiyo (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This research aims to explore the strategies of BMM and BSI Maslahat in optimizing accountability and transparency in digital waqf instruments. This research uses a qualitative approach with two case studies, where the data collected is then analyzed using the Miles, Huberman, and Saldana modeling technique with the help of the NVivo 12 application. Using the Theory of sharia governance as a grand Theory, this research produces findings on the strategies carried out by both institutions in optimizing accountability and transparency, namely: conducting regular independent audits, forming an independent oversight committee, implementing the Waqf Core Principles (WCP), providing an online platform, involving all stakeholders, providing open financial reports on the website, and implementing a blockchain-based reporting system. By exploring and analyzing institutional strategies for accountability and transparency in waqf management through digital waqf instruments, this research can provide new insights into understanding the growing phenomenon of waqf fund management. In addition, the results of this study can be utilized by the general public as information that can be utilized by the general public as information that can increase public trust and participation in giving cash waqf. Therefore, this research argues that strengthening accountability and transparency will optimize digital waqf fundraising instruments to encourage the growth of waqf in Indonesia